Global software and IT : a guide to distributed development, rightshoring, and outsourcing - Ebert, Christof (Hoboken, N.J. : Wiley, 2011)
"Global software engineering, implying both internal and outsourced development, is a fast-growing scenario within industry; the growth rates in some sectors are more than 20% per year. However, half of all offshoring activities are cancelled within the first 2 years, at tremendous unanticipated cost to the organization. This book will provide a more balanced framework for planning global development, covering topics such as managing people in distributed sites, managing a project across locations, mitigating the risk of offshoring, processes for global development, practical outsourcing guidelines, collaboration, and communication. Drawing on the author's vast experience, it shares best practices and survival strategies from projects of various types and sizes that involve different continents and diverse cultures"--
"This book will provide a more balanced framework for planning global development, covering topics such as managing people in distributed sites, managing a project across locations, mitigating the risk of offshoring, processes for global development, practical outsourcing guidelines, collaboration, and communication"--
Strategy. Different Business Models -- The Bright Side: Benefits -- The Dark Side: Challenges -- Deciding the Business Model -- Preparing the Business Case -- Development. Requirements Engineering -- Estimation and Planning -- Development Processes -- Practice: Global Software Architecture Development / Daniel J Paulish -- Practice: Software Chunks and Distributed Development / Audris Mockus AvayaLabs, David M Weiss -- Configuration Management -- Open Source Development -- Quality Control -- Tools and IT Infrastructure -- Practice: Collaborative Development Environments / Fabio Calefato, Filippo Lanubile -- Management. Life-Cycle Management -- Supplier Selection and Evaluation -- Supplier Management -- Practice: IT Outsourcing--A Supplier Perspective / S M Balasubramaniyan -- Monitoring Cost, Progress, and Performance -- Risk Management -- Practice: Risk Assessment in Globally Distributed Projects / Adailton Lima, Alberto Avritzer -- Intellectual Property and Information Security -- Practice: Global Software Engineering in Avionics / Werner Burger, Diehl Aerospace -- Practice: Global Software Engineering in Automotive / Andree Zahir, Satish Seetharam -- People and Teams. Work Organization and Resource Allocation -- Roles and Responsibilities -- Soft Skills -- Training and Coaching -- Practice: People Factors in Globally Distributed Projects / Bikram Sengupta -- Practice: Requirements Engineering in Global Teams / Daniela Damian, Sabrina Marczak, Irwin Kwan -- Practice: Educating Global Software Engineering / Gopalaswamy Ramesh, Chandrashekar Ramanathan, Sowmyanarayanan Sadagopan -- Advancing your Own Business. Key Take-Away Tips -- Global Software and IT Rules of Thumb -- The World Remains Flat -- Appendices. Appendix A: Checklist/Template: Getting Started -- Appendix B: Checklist/Template: Self Assessment -- Appendix C: Checklist/Template: Risk Management.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Computer software -- Development; Project management; Computer software industry; Gestion de projet; Logiciels -- Industrie; BUSINESS & ECONOMICS -- Outsourcing; Computer software -- Development; Computer software industry; Project management